The effect of bowel preparation on the outcomes of scheduled colorectal surgery: a comparative study - kanaan, samir (Latakia University Journal -Medical Sciences Series, 2023)
This scientific study aims to evaluate the effects of bowel preparation on the outcomes of scheduled colorectal surgery. The study included a group of 83 patients, 37 without bowel preparation and 46 with bowel preparation. Perioperative outcomes of patients were evaluated, including surgical site infection (SSI) rates, postoperative complications, and length of hospital stay. The results concluded that bowel preparation before scheduled colorectal surgery has no superiority in reducing SSI and postoperative complications (anastomotic leakage, occurrence of abdominal or pelvic abscesses), as well as shortening the length of hospital stay, and did not show any clear advantage over the patients without mechanical bowel preparation.